Standard Operational Procedures for Congregational Services During The Covid-19 Pandemic at The Head Office Of Shafira Tour Travel Surabaya. - Ahmad Yahya; Imas Maesaroh (Proceedings of International Conference on Da'wa and Communication, 2021)
This study aims to see the standard operating procedures for services performed by Shafira Tour Travel Surabaya during the covid-19 pandemic. First, to see how the operational standards were enforced before the pandemic. Second, to see how the differences in services after the pandemic are seen from the planning changes and innovations that Shafira made during the covid-19 pandemic. In this study, the authors used qualitative research methods. The qualitative method is used because it is considered practical to describe and explain service procedures before the pandemic. Then, for data collection techniques, the author uses triagulation techniques, namely data collection by observing, utilizing documentation, and interviews. The results of this study explain that Shafira before the pandemic had carried out service standards in accordance with those set by the government. Then for planning changes, Shafira has done for the good and did it gradually and carefully, but the leadership did not involve employees who were affected by changes in the work system. Then, the innovations made were by changing the work system and implementing health protocols, but not increasing digital capabilities because they had done it before the pandemic.